How do International Volunteering Characteristics Influence Outcomes? Perspectives from Partner Organizations - Lough, Benjamin J.; Tiessen, Rebecca (Voluntas (Manchester, England), 2018)
This study examines how different types of international volunteering influence common program outcomes such as building organizational capacity, developing international relationships, and performing manual labor. Survey responses were collected from 288 development-oriented volunteer partner organizations operating in 68 countries. Data on the duration of volunteer service, the volunteers' skill levels, and other variables were used to develop a rough typology of international volunteering. Binary logistic regression models then assessed differences in outcomes across five volunteering types. Findings suggest that future research needs to be more precise about how the nuances and complexity of diverse forms of international volunteering influence outcomes.